(3cJGH GdaUd aj Gdedd hGdBQGA hGdfMds - (3Ydj Hf CMeO Hf SYjO Hf MRe GdXGgQj, GHf MRe , CHh eMeO ,J (B456 (3g` s
(3ChdgG (B:s
(3jHJOF HGdcdGe gd TGA Gddg YR hLd chf GdcaQ hGdaSb Ce de jTC Pdc s
(3BNQgG (B:s
(3aGdMjhGf dG jJhGdO ai GdeGA hMOg hdG ai GdGQV hMOgG hdcf eeG jLJeY ef GdGQV hGdeGA eYkG aJHGQc Gddg QH GdYGdejf dG Edg EdG gh GMSf GdNGdbjf Ld hYR hHGddg GdJhajb Ydi cd MGd s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B254 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B17 - (3U (B16s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B2 - (3U (B319s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI SjFI s
(3GdfSNI HgG JdhjK , CQVg s
Keywords: (3GdJhMjO hGdedd hGdfMds